2018
DOI: 10.1007/s12328-018-0881-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia-induced pancreatitis: updated review of current treatment and preventive strategies

Abstract: Hypertriglyceridemia (HTG) is an uncommon but well-established cause of acute pancreatitis (AP) comprising up to 7% of the cases. The clinical course of HTG-induced pancreatitis (HTGP) is highly similar to that of AP of other etiologies with HTG being the only distinguishing clinical feature. However, HTGP is often correlated with higher severity and elevated complication rate. At present, no approved treatment guideline for the management of HTGP is available, although different treatment modalities such as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 54 publications
2
138
0
13
Order By: Relevance
“…Устойчиво повышенный уровень инсулина также может привести к дислипидемии [18]. Одна из разновидностей дислипидемии -гипертриглицеридемия, характеризуется устойчивым повышением уровня ТГ в сыворотке крови натощак, и является одним из критериев диагностики МС [33,34]. Повышенный уровень ТГ имеет взаимосвязь с развитием атеросклероза даже в отсутствие гиперхолистеринемии [35].…”
Section: вирусы и бактерии -инициаторы ос и воспаленияunclassified
“…Устойчиво повышенный уровень инсулина также может привести к дислипидемии [18]. Одна из разновидностей дислипидемии -гипертриглицеридемия, характеризуется устойчивым повышением уровня ТГ в сыворотке крови натощак, и является одним из критериев диагностики МС [33,34]. Повышенный уровень ТГ имеет взаимосвязь с развитием атеросклероза даже в отсутствие гиперхолистеринемии [35].…”
Section: вирусы и бактерии -инициаторы ос и воспаленияunclassified
“…Hypertriglyceridemia occupies the third position among the causes of AP (2%-5%) in the absence of other etiological factors, with a risk factor of 1.5%, and when the levels are >1000 mg/dL, the risk increases to 20.2%. Type I, IV, and V dyslipidemia have also been reported to be associated with AP (Frederickson Classification) [12].…”
Section: Etiologymentioning
confidence: 99%
“…The use of heparin (preferably the one with low molecular weight) in moderately severe to severe AP has been associated with better evolution with a lower incidence of necrosis, ability to improve pancreatic microcirculation and anti-inflammatory effect through a reduction in the stimulation of macrophages and monocytes [89]. Additionally, experimental studies have revealed that heparin reduces the levels of amylase, endothelin-1, inflammatory cytokines, and TNF-α, and causes the activation of NF-kB [12]. Simvastatin has been reported as a promising drug for the prophylaxis of new episodes in recurrent AP [12].…”
Section: Other Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…SIRS is the cause of bacterial (Gram negative) translocation from the patient's colon. 1,2,8,12 No single laboratory or clinical sign is pathognomonic for acute pancreatitis. Many bio-markers and inflammatory mediators for predicting the severity of acute pancreatitis are being evaluated.…”
Section: Assessment Of Severity and Advantages Of Modified Ct Severitmentioning
confidence: 99%